End of days : ethics, tradition, and power in Israel - Manekin, Mikhael (Academic Studies Press, 2023)
"End of Days (translated from the recently published Hebrew book, Atchalta) is both a meditation on Jewish morality in the age of Israeli Jewish power, and a cri du coeur by an Orthodox Israeli Jew, a former combat officer in the IDF, for Israelis to look into the Jewish religious ethical tradition for an alternative to the secular and religious Zionism that sanctifies power, statehood, and sovereignty. Appealing to a wealth of Jewish sources from the Bible to the present, including medieval Jewish ethical literature, rabbinic sources, Jewish law, and contemporary Israeli thought, the book presents an argument against the Israeli's occupation of the Palestinian people and the suppression of their rights from the perspective of a modern Israeli religious Jew"-- Provided by publisher.
Keywords: Arab-Israeli conflict -- Religious aspects -- Judaism.; Arab-Israeli conflict -- Moral and ethical aspects.; Jewish ethics -- Political aspects.; Conflit israélo-arabe -- Aspect religieux -- Judaïsme.; Conflit israélo-arabe -- Aspect moral.; Morale juive -- Aspect politique.; SOCIAL SCIENCE / Jewish Studies.; Arab-Israeli conflict -- Moral and ethical aspects; Arab-Israeli conflict -- Religious aspects -- Judaism; Electronic books.